1994
DOI: 10.1111/j.1365-2427.1994.tb00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the distribution and abundance of an unpigmented heterotrophic alga Prototheca richardsi

Abstract: SUMMARY 1. Numbers of the contramensal alga Prototheca richardsi were high in spring in two ponds used for breeding by anuran amphibians, but lower at other times of year and undetectable in two ponds not used by anurans. 2. Prototheca richardsi became abundant in the silt of eight experimental ponds which contained tadpoles, but remained undetectable in four otherwise identical ponds lacking tadpoles. 3. Prototheca richardsi numbers in laboratory microcosms remained stable for many days in sterile tap water,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Mean cell size, utilization of carbon sources, and other growth parameters were consistent with classification of the anuran parasite in the genus Prototheca (Wong & Beebee, 1994). Furthermore, DNA-RNA hybridization studies (Beebee, 1991) showed stronger heterologous binding with nucleic acids from a green alga (genus Dunaliella) than with those from yeast or protozoa (genera (Wong & Beebee, 1994). Other protothecans can be cultured in uitro on Pvototheca isolation medium (PIM) (Pore, 1973), whereas P. richardsi shows only weak growth.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Mean cell size, utilization of carbon sources, and other growth parameters were consistent with classification of the anuran parasite in the genus Prototheca (Wong & Beebee, 1994). Furthermore, DNA-RNA hybridization studies (Beebee, 1991) showed stronger heterologous binding with nucleic acids from a green alga (genus Dunaliella) than with those from yeast or protozoa (genera (Wong & Beebee, 1994). Other protothecans can be cultured in uitro on Pvototheca isolation medium (PIM) (Pore, 1973), whereas P. richardsi shows only weak growth.…”
Section: Introductionmentioning
confidence: 57%
“…Algae of the genus Prototheca (Kruger, 1894) have spherical unpigmented cells 2-10 pm in diameter, distinctive cell walls, and refractive, inclusion-bearing vacuoles that restrict the cytoplasm to the edges of the cell (Pore, 1985(Pore, , 1986Beebee, 1991). Mean cell size, utilization of carbon sources, and other growth parameters were consistent with classification of the anuran parasite in the genus Prototheca (Wong & Beebee, 1994). Furthermore, DNA-RNA hybridization studies (Beebee, 1991) showed stronger heterologous binding with nucleic acids from a green alga (genus Dunaliella) than with those from yeast or protozoa (genera (Wong & Beebee, 1994).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations